DEBRIDEMENT SEBAGAI TATALAKSANA ULKUS KAKI DIABETIK - Darmaputra Wesnawa, Made Agustya (E-Jurnal Medika Udayana, 2014)
Reported a case of female patient 45 years old with diagnose Diabetes Mellitus Type 2 with Diabetic Foot Ulcer Wagner grade 2 at region pedis dextra. Debridement was done in this patient. The type of debridement was surgical debridement. The purpose of this procedure is to remove necrotic tissue and hyperkeratosis until reach the health tissue. After debridement, the wound was dressed with kassa sterile and elastic bandage. During treatment, there were no pus, bleeding, and unpleasant odor on wound, granulation tissue begin to appear, and pain on the pedis was reduced.
Keywords: diabetic foot ulcer, debridement, diabetes mellitus